Study on functional cooperation between ACS air carriers to promote trade and travel between the ACS - El Perial Management Services (CCS GeorgetownGY, 1995)
Posits that easy access to affordable air transportation is critical to the fulfillment of the ACS vision. Reviews the current economic and air transportation environments within the region, and concludes that the requirement is to profitably provide a readily differentiated and significantly higher quality service to the travelling and cargo shipping communities at lower tarrifs. Makes recommendations to the public and private sectors.